N-chlorotaurine Inactivates Acanthamoeba and Candida albicans in the Porcine Ex Vivo Corneal Infection Model. Issue 8 (August 2019) - Teuchner, Barbara; Wibmer, Idris D.; Schaumann, Philipp; Seifarth, Christof; Walochnik, Julia; Nagl, Markus
Abstract : Purpose: N -chlorotaurine (NCT) is an anti-infective belonging to the class of chloramines and an investigative drug for the topical treatment of keratoconjunctivitis. The aim of the present study was to demonstrate its efficacy against Acanthamoeba and Candida in corneas infected ex vivo. Methods: Corneal buttons from porcine eyes were contaminated with Acanthamoeba castellanii trophozoites or Candida albicans Centraalbureau voor Schimmelcultures 5982 and incubated for 7 and 3 days, respectively. Subsequently, they were treated with 1% NCT for 5 to 120 minutes. After further incubation for 2 days in the absence of NCT in tests with A. castellanii, the buttons were homogenized, and the amoebae grown for a further 5 days before they were counted in a light microscope. For C. albicans, quantitative cultures were performed from corneal homogenates. Results: Incubation of 120 minutes in NCT completely inhibited the regrowth of A. castellanii and reduced the number of C. albicans colony-forming unit counts by 4 log10 . In addition, at 60 minutes, significant reductions of both pathogens could be observed. Histology showed penetration of pathogens into the stroma of the corneal buttons. Conclusions: NCT inactivates A. castellanii and C. albicans in corneal tissue.